The Effect of Squat Training and Leg Length in Increasing the Leg Power of Volleyball Extracurricular Participants - Ahmad Nasrulloh; Putri Deviana; Rina Yuniana; Kukuh Wahyudin Pratama (Physical Education Theory and Methodology, 2021)
The study purpose. This study aims to see: (1) The difference in the effect of barbell squat and resistance band squat exercises on the increase in leg power. (2) The difference in influence between players who have high leg height and low leg length on the increase in leg power. (3) The interaction of barbell squat and resistance band squat exercises with leg length (high and low) to increase the power of volleyball extracurricular participants.